Thou shalt not bear false witness against your customers: Cultural norms and the Volkswagen scandal - Iftekhar Hasan; Felix Noth; Lena Tonzer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
This paper investigates whether cultural norms shaped by religion drive consumer decisions after a corporate scandal. We exploit the unexpected notice of violation by the US Environmental Protection Agency in September 2015, accusing the car producer Volkswagen (VW) to have used software to manipulate car emission values during test phases. Using a difference-in-difference model, we show that new registrations of VW (diesel) cars decline significantly in German counties with a high share of Protestants following the VW scandal. Our results suggest that the enforcement culture rooted in Protestantism affects consumer decisions and penalises corporate fraud.
urn:nbn:de:gbv:3:2-113431; Additional information: A revised version of this paper has been published as Hasan, Iftekhar; Noth, Felix; Tonzer, Lena: Cultural Norms and Corporate Fraud: Evidence from the Volkswagen Scandal. IWH Discussion Paper 24/2020. Halle (Saale) 2020: http://hdl.handle.net/10419/226484; More recent version: http://hdl.handle.net/10419/226484
Keywords: D12; O30; Q50; Z12; 330; religion; corporate scandal; consumer choice; climate change